Answer:
a = 6/5
b = 7/8
c = 1/5
Explanation:
We want to make two of these equations be in terms of the same variable, so let's solve the first and third in terms of b.
5a-24b=-15 -> -3 + 24b/5 = a
48b+35c = 49 -> 49/35 - 48b/35 = 7/5 - 48b/35 = c
Now we can replace the a and c in the second equation and solve for b.
10a+45c=21
10(-3+24b/5)+45(7/5 - 48b/35) = 21
-30 + 48b + 63 - 432b/7 = 21 -> -12 = -96b/7 -> b=7/8
Now we can plug b back into the other two to solve for a and c. I will leave that to you unless you would like the steps there.